Appalachian Health : Culture, Challenges, and Capacity - Wykoff, Randolph; Scutchfield, F. Douglas (Book collections on Project MUSE., 2022)
"Appalachian Health explores major challenges and opportunities for promoting the health and well-being of the people of Appalachia, a historically underserved population. It considers health's intersection with social, political, and economic factors to shed light on the trends affecting mortality and morbidity among the region's residents. Editors F. Douglas Scutchfield and Randy Wykoff have assembled high-profile experts working in academia, public health, and government to offer perspectives on a wide range of topics including health behaviors, environmental justice, and pandemic preparedness. This volume also provides updated data on issues such as opioid abuse, "deaths of despair," and the social determinants of health. Together, the contributors illuminate the complex health status of the region and offer evidenced-based programs for addressing the health problems that have been identified"--